Urbanization in a ‘Least Developed’ Country - Singh, Ram Bali (National Geographical Journal of India, 2022)
Divergence of opinions exists regarding the role of urbanization in national development especially in developing countries. Ethiopia, classified by the UN as a ‘least developed country’ is one of the least urbanized countries in the continent of Africa but is experiencing the highest rate of urbanization. The pattern of urbanization is uneven in terms of regional and population size distribution of towns and the urban system is functionally unarticulated having weak rural-urban and urban-urban linkages. Simultaneously urban areas are expanding due to natural increase as well as rural-urban migration, the latter being driven out by a languishing rural-agricultural sector. Rural-urban migration is putting high pressure on urban areas unable to offer jobs, shelter and services to the new migrants. Slum and squatter settlements are expanding, urban informality is growing, land speculation is rampant and the urban environmental conditions are becoming bad to worse. The present paper discusses these aspects of urbanization and urban growth and concludes with the initiatives taken by the government to ameliorate the situation.